Structure of metabotropic glutamate receptor C-terminal domains in contact with interacting proteins - Enz, Ralf (Frontiers in Molecular Neuroscience, 2012)
Metabotropic glutamate receptors (mGluRs) regulate intracellular signal pathways that control several physiological tasks, including neuronal excitability, learning and memory. This is achieved by the formation of synaptic signal complexes, in which mGluRs assemble with functionally related proteins such as enzymes, scaffolds and cytoskeletal anchor proteins. Thus, mGluR associated proteins actively participate in the regulation of glutamatergic neurotransmission. Importantly, dysfunction of mGluRs and interacting proteins may lead to impaired signal transduction and finally result in neurological disorders, e.g. night blindness, addiction, epilepsy, schizophrenia, autism spectrum disorders and Parkinson´s disease. In contrast to solved crystal structures of extracellular N-terminal domains of some mGluR types, only a few studies analyzed the conformation of intracellular receptor domains. Intracellular C-termini of most mGluR types are subject to alternative splicing and can be further modified by phosphorylation and SUMOylation. In this way, diverse interaction sites for intracellular proteins that bind to and regulate the glutamate receptors are generated. Indeed, most of the known mGluR binding partners interact with the receptors´ C-terminal domains. Within the last years, different laboratories analyzed the structure of these domains and described the geometry of the contact surface between mGluR C-termini and interacting proteins. Here, I will review recent progress in the structure characterization of mGluR C-termini and provide an up-to-date summary of the geometry of these domains in contact with binding partners.